Recognizing the trends and driving forces influencing the future of scientometrics education in Iran - Ebrahim Emami Qaratapeh; Farideh Osareh; Saeedeh Ebrahimi; Zahra Asemani (تصمیم گیری و تحقیق در عملیات)
Purpose: Like other sub-disciplines of humanities, scientometrics is influenced by significant factors leading to Belief in Favorable Future (BFF). Education in the field of scientometrics should always strive to prolong its survival and guarantee its evolution in the coming years. Hence, the excellence of scientometrics requires constant and undivided attention to both external and internal contributing factors. The principal objective of this study is to recognize the underlying trends and driving forces influencing the future of scientometrics education in Iran.Methodology: A meta-analysis of contingent surveys is conducted to serve the purpose of practicality. The expert panel is comprised of 15 professionals in knowledge and information science. Subsequently, a researcher-constructed questionnaire was distributed among professionals.Findings: The research findings demonstrated that the driving forces influencing the future of scientometrics education in Iran could be categorized into eleven general indicators. Seven internal indicators include philosophy and the model of higher education for scientometrics, educational forces, curriculum, services and facilities, information and communication technology, academic level of universities, and specific field challenges. Four external indicators include sociological, economic, information technology, policy-making, and higher education system management. Altogether, both internal and external factors are sub-categorized into 57 items.Originality/Value: Due to inconvenient circumstances of scientometrics education in Iran, policymakers and managers of the Iranian higher education system are duly required to address the need to transform the ongoing trends and functional driving forces in the field of scientometrics.